Energy Control Strategy for Plug-in Hybrid Electric Bus Based on Lithium Battery Cycle Life - WANG Wenming; PENG Zaiwu; SONG Chao; WEN Jianfeng; YANG Jiejun; WEN Duo (Kongzhi Yu Xinxi Jishu)
It presented an energy control strategy for plug-in series hybrid electric bus, in view of the limited battery cycle life. In the stage of charge-sustaining, the vehicle controller mainly adopts the power following strategy, combined with counting up the charge and discharge Ah of lithium battery, and controls the output power of APU system, then achieves self balancing of power system. According to the statistical data of daily mileage and the amount of Ah flowing through the lithium battery, the vehicle control strategy automatically adjusts the charging current limit to the lithium battery system, so as to control the energy flowing through the lithium battery, and achieves the purpose that lithium battery cycle times meet the vehicle life cycle. Although the fuel consumption of the vehicle increases with a certain extent under specific working conditions, however, the cost of the vehicle is lower during the life cycle.